Biological control of Sitotroga cerealella in stored corn using Trichogramma pretiosum and Bracon hebetor - Nava, D.E.=700 1 Parra, J.R.P.
(Es, En)
Ilus., 34 ref.
Keywords: SITOTROYA CEREALELLA; CONTROL BIOLOGICO; PLAGAS DE PRODUCTOS ALMACENADOS; PARASITOS; LARVAS; ESPAÑA; PARASITO DE HUEVOS; PARASITO DE LARVAS; BOLETIN DE SANIDAD VEGETAL: PLAGAS